Social Safety Nets, Economic Freedom and Public Policy - Simrit Kaur (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
What is the relationship between social welfare, safety nets and economic freedom? Arguably, if economic freedom (EF) promotes growth and if it trickles down EF promotes larger freedoms (e.g. a healthy and productive life, free from want and deprivation). However, higher EF by definition entails lower government interventions in sectors such as provision of safety nets, health and education, thereby curtailing some aspects of larger freedoms. Thus ambiguity exists with respect to the effect of EF on larger freedoms. Given that developing countries account for many poor, have malnourished children, face a decline in per capita availability of food grains, with a sharp rise in farmer's suicide (for instance in India), providing safety nets is essential for enhancing larger freedoms. However, with the initiation of economic reforms favouring market oriented policies, the role of the government in investment decisions has diminished. The econometric analysis suggests that higher levels of EF promote not only higher levels of GDP per capita but also impact larger freedoms favourably. However, results also confirm that higher levels of EF associated with few of its sub-components, particularly lower government consumption expenditures and lower transfers and subsidies, affect larger freedoms adversely. Since the role of the State in creating and expanding social opportunities, and in mitigating risks and vulnerability from the broader perspective of human freedoms is well documented, a policy dilemma exists regarding the appropriate level of EF. In light of this dilemma, and acknowledging that public action expands larger freedoms, the paper questions the commonly held belief that government interventions are necessarily less productive.
Keywords: I30; I38; O43; 330; Economic freedom; safety nets; human development; income inequality; deprivation; public intervention